A Unified Approach to BER Analysis of Synchronous Downlink CDMA Systems with Random Signature Sequences in Fading Channels with Known Channel Phase. (6th February 2008) - Moinuddin Moinuddin, M. M.; Sheikh Sheikh, A. U. H. A. U. H.; Zerguine Zerguine, A. A.; Deriche Deriche, M. M.
Abstract : A detailed analysis of the multiple access interference (MAI) for synchronous downlink CDMA systems is carried out for BPSK signals with random signature sequences in Nakagami-m fading environment with known channel phase. This analysis presents a unified approach as Nakagami-m fading is a general fading distribution that includes the Rayleigh, the one-sided Gaussian, the Nakagami-q, and the Rice distributions as special cases. Consequently, new explicit closed-form expressions for the probability density function (pdf ) of MAI and MAI plus noise are derived for Nakagami-m, Rayleigh, one-sided Gaussian, Nakagami-q, and Rician fading. Moreover, optimum coherent reception using maximum likelihood (ML) criterion is investigated based on the derived statistics of MAI plus noise and expressions for probability of bit error are obtained for these fading environments. Furthermore, a standard Gaussian approximation (SGA) is also developed for these fading environments to compare the performance of optimum receivers. Finally, extensive simulation work is carried out and shows that the theoretical predictions are very well substantiated.